Correlative Analysis of TOEFL iBT Scores of Listening Skill Versus Scores of Business English Speaking Skill among Binus University Sophomores - Almodad Biduk Asmani (Lingua Cultura, 2014)
Article found out whether BINUS university sophomore’s TOEFL iBT scores of Listening skill are correlated with those of speaking skill. The research project was expected to result in the best teaching technique of delivering conversational tasks at BINUS University by using alternative approaches of integrated, isolated, or mixed skills. The research project applied the descriptive approach of quantitative method, and thus depends on numerical data. The research project examined the set of data under two skills of the same class groups, which were to compare the listening scores with the speaking ones. Then, the degree of correlation of the two skills was tested so as to find its significance. Interpretation and explanation of data was made based on the statistical results by using correlation research analysis. Based on the statistical results, the listening scores significantly correlated with those of the speaking skill, and there is a moderately linear relationship between these paired scores.